Scanning the impacts of cryptocurrencies on the future of the Finnish banking sector : Three scenarios - Sciurca, Enrico (My University, 2023)
Cryptocurrencies popularity have increased during the last few years. This thesis aims in scanning the possible impacts of cryptocurrencies in the future of the Finnish banking sector during the next ten years by producing future scenarios. A two rounded disaggregative policy Delphi study was conducted to gather experts’ opinions on the topic. The first round of the Delphi process consisted of a survey that included qualitative and quantitative questions. The qualitative questions were open ended questions, and the quantitative questions asked the panellists their views on prob-able and preferred futures states on a numerical scale. The survey was made with litera-ture regarding the topics of Finnish banking and cryptocurrencies. In addition, literature on the case of the European Central Bank launching its own virtual currency in the fu-ture was used in producing the survey. The results of the first survey were studied with a cluster analysis. The results of the cluster analysis were used to produce four images of the future that were commented by the experts in the second round of the Delphi process. The results of the conducted Delphi study were used to produce three scenarios, the scenarios were created using the method of the futures table. The three final scenarios are “Business as usual”, “Technological innovation” and “Decentralized movement”.

Kryptovaluuttojen suosio on kasvanut viimeisten vuosien aikana. Tämän tutkielman tarkoitus on selvittää kryptovaluuttojen vaikutukset suomalaisen pankkisektorin tulevai-suuteen seuraavan kymmenen vuoden aikana. Kaksiosainen erittelevää Delfoi-menetelmää käyttävä paneeli suoritettiin asiantuntijoiden näkemyksien keräystä varten. Ensimmäinen Delfoi-paneeli oli kysely, joka sisälsi kvalitatiivisia ja kvantitatiivisia kysymyksiä. Kvalitatiiviset kysymykset olivat rajaamattomia avoimia kysymyksiä. Kvantitatiiviset kysymykset esittivät panelisteille heidän näkemyksensä todennäköisestä ja toivotusta tulevaisuudesta numeerisilla asteikoilla. Kysely luotiin Suomen pankkisektorista ja kryptovaluutoista käsittelevän kirjallisuuden avulla. Lisäksi hyödynnettiin kirjallisuutta, joka käsitteli Euroopan keskuspankin mah-dollisuutta lanseerata oma virtuaalivaluutta tulevaisuudessa. Ensimmäisen Delfoi-paneelin vastaukset analysoitiin klusterianalyysillä. Klusterianalyysin tulokset käytettiin neljän tulevaisuuskuvan luomiseen. Asiantuntijat kommentoivat tulevaisuuskuvia Delfoi-paneelin toisessa osassa. Tulokset, jotka saatiin suoritetusta Delfoi-paneelista, toimivat pohjana kolmelle ske-naariolle. Skenaariot luotiin tulevaisuustaulukkomenetelmällä. Luodut kolme skenaariota nimettiin seuraavasti: ”Normaalia liiketoimintaa”, ”Teknologista innovaatiota” ja ”Hajautettu liike”.
Keywords: Cluster analysis, cryptocurrencies, Delphi study, disaggregative Delphi, Finnish banking sector, futures studies, futures table, images of the future, scenarios